TrASDition Training: An online parental training for transition-age youth with autism spectrum disorder. (June 2021) - Martina, Siracusano; Jonathan, Calsolaro; Assia, Riccioni; Leonardo, Gialloreti Emberti; Arianna, Benvenuto; Giulia, Giovagnoli; Paolo, Curatolo; Luigi, Mazzone
Highlights: Transition age is a challenging period for autistic youth and their parents. Reduced rates of employment and self-sufficiency are reported in adult age. Parental well-being can influence education, behavioral and developmental trajectories. Family centered interventions are considered promising models. Abstract: Transition to the adult age represents a rather challenging period of life for youth with Autism Spectrum Disorder (ASD) and for their families. Given the actual lack of integrated healthcare systems for autistic young-adults, enhancing parental skills could represent a feasible program to improve skills preparatory for transition in adult life. The online approach, providing easy access to services which otherwise would burden a daily family organization, already strenuous for a family with an autistic person, can represent an innovative way of delivering intervention. Therefore, we developed an online psychoeducational parental training, named TrASDition Training, with a 6 months duration, addressed to parents of autistic youth with and without Intellectual Disability during the transition age. The aim of this study was to longitudinally evaluate the impact of the online parental training on the adaptive functioning, on the repetitive and problematic behaviors of ASD youth (n = 23) and on parental stress. After 6 months of Training, we found a significant improvement in adaptive functioning of ASD participants and a reduction of parental stress.